A comparison of hypothesis testing procedures for two population proportions - Hort, Molly (Kansas State University, 2008)
It has been shown that the most straightforward approach to testing for the difference of two independent population proportions, called the Wald procedure, tends to declare differences too often. Because of this poor performance, various researchers have proposed simple adjustments to the Wald approach that tend to provide significance levels closer to the nominal. Additionally, several tests that take advantage of different methodologies have been proposed. This paper extends the work of Tebbs and Roths (2008), who wrote an R program to compare confidence interval coverage for a variety of these procedures when used to estimate a contrast in two or more binomial parameters. Their program has been adapted to generate exact significance levels and power for the two parameter hypothesis testing situation. Several combinations of binomial parameters and sample sizes are considered. Recommendations for a choice of procedure are made for practical situations.
Keywords: proportion; hypothesis test; empirical bayes methods; Wald; Statistics (0463)